Building the Museum of the Person from RDF Triples and SPARQL - Araújo, Cristiana Esteves; Martini, Ricardo Giuliani; Henriques, Pedro Rangel; Almeida, José João (Revista ComInG - Communications and Innovations Gazette, 2016)
The Museum of the Person (MP) is a virtual museum that aims to show life stories of people, whether they are famous or anonymous. Its repository contains a collection of interviews, in XML (eXtensible Markup Language). Each interview tells the story of a person's life, describing events and other special situations that person has participated. The main objective is to on build web pages that carry out the museum exhibition rooms. To feed the exhibition rooms it is necessary to (automatically) extract the information included in the repository. Initially was constructed an ontology specific to the repository of the Museum of the Person, designated OntoMP. Then we adopted a standard to create ontologies for museums, CIDOC-CRM (CIDOC - Conceptual Reference Model) refined with FOAF (Friend of a Friend) and DBpedia to represent OntoMP. This article aims to discuss the construction of virtual rooms using a TripleStore to store the repository information and SPARQL technology (SPARQL Protocol and RDF Query Language) to extract information from the XML repository.